Outcomes of acute appendicitis in patients younger than age 4: a descriptive study - Jhon Camacho-Cruz; Patricia Ocampo Padilla; Daniela Guerrero Sánchez; Diana Milena Mongui; Laura Katherine Hoyos; María Lucia Porras; Pablo Vásquez Hoyos; Fernando Polo; Carlos Alberto Castro (SpringerOpen, 2022)
Abstract Background Acute appendicitis is an infrequent pathology in children under 4 years of age, and its diagnosis is a clinical challenge that can lead to late detection. The intention of this study is to describe the clinical and surgical findings and to explore factors and outcomes associated with appendiceal perforation in patients under 4 years of age with histologically confirmed acute appendicitis. Cross-sectional study of historical data is on patients with a pathologic diagnosis of appendicitis. Clinical, surgical, and pathological variables were described. The relationship between the presence of perforation and associated factors and outcomes was explored using odds ratios (OR) and 95% confidence intervals. Results Seventy-five patients were found between 2013 and 2019. Seventy-four cases presented with pain on palpation, 56 (75%) with signs of peritoneal irritation, and 70 (93%) with sepsis on admission to the emergency room. An ultrasound was done on 57 patients (76%), and only 26 (45%) were suggestive of appendicitis. Forty-one (55%) cases were operated on by open surgery and 34 (45%) by laparoscopy. In 61 (81%), they were perforated, and 48 (64%) presented peritonitis. Perforation was associated with increased hospital days (OR = 2.54 [1.60−4.03]), days of antibiotics (OR = 4.40 [2.09−9.25]), and admission to intensive care (OR = 9.65 [1.18−78.57]). Conclusions Abdominal pain reported by parents, pain on abdominal palpation, and clinical criteria of sepsis on admission to the emergency room are common features. Acute appendicitis complicated by perforation leads to high morbidity due to longer antibiotic treatment, hospitalization days, admission to PICU, and postoperative ileus.